Prevalence of Low Birth Weight and Its Developmental Vulnerability Among Infants in Nepal: A Critical Review of the Literature and Future Recommendations - Sangita Pudasainee-Kapri (Journal of Nepal Medical Association, 2025)
Limited research has focused on developmental vulnerability of low birth weight (LBW) infants in Nepal. This review analyzes the prevalence and magnitude of LBW in Nepal followed by developmental vulnerabilities and the economic impact of LBW.